2021
DOI: 10.3233/jpd-212720
|View full text |Cite
|
Sign up to set email alerts
|

Locus Coeruleus Degeneration Correlated with Levodopa Resistance in Parkinson’s Disease: A Retrospective Analysis

Abstract: Background: The widely divergent responsiveness of Parkinson’s disease (PD) patients to levodopa is an important clinical issue because of its relationship with quality of life and disease prognosis. Preliminary animal experiments have suggested that degeneration of the locus coeruleus (LC) attenuates the efficacy of levodopa treatment. Objective: To explore the relationship between LC degeneration and levodopa responsiveness in PD patients in vivo. Methods: Neuromelanin-sensitive magnetic resonance imaging (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…We demonstrated a significant relationship between LC degeneration and functional organization of the motor cortex. In addition, we demonstrated a significant relationship between LC degeneration and motor response to levodopa in recent published paper ( Zhou et al, 2021 ). Therefore; the interactions between the dopaminergic and noradrenergic systems require further investigation.…”
Section: Discussionsupporting
confidence: 64%
“…We demonstrated a significant relationship between LC degeneration and functional organization of the motor cortex. In addition, we demonstrated a significant relationship between LC degeneration and motor response to levodopa in recent published paper ( Zhou et al, 2021 ). Therefore; the interactions between the dopaminergic and noradrenergic systems require further investigation.…”
Section: Discussionsupporting
confidence: 64%
“…Notably, we found that subtype 1 showed a signi cantly poor response to levodopa replacement therapy than subtype 2, which may suggest the different pathobiological mechanisms. In consistent with this nding, recent animal and human studies have shown that the de ciency of LC-noradrenergic system could complicate PD symptoms and diminishes the therapeutic e cacy of levodopa 33,44 . We also found that subtype 2 showed signi cant damage of perfusion and functional synchronization in cortical regions.…”
Section: Clinical and Neurodegeneration Trajectories Of Twosupporting
confidence: 65%
“…Therefore, we used the NM-MRI to measure the degeneration of SN and LC. According to previous method, we calculated the contrast to noise ratio of the SN (CNR SN ) and LC (CNR LC ), which represented the integrity of SN and LC 33 . A lower CNR value means more serious degeneration.…”
Section: Neuromelanin Sensitive Image Processingmentioning
confidence: 99%
“…There was an association between regional structural degeneration and individual expressions of PD nonmotor symptoms (such as orthostatic dysregulation or apathy) 43 . Another group found a significant positive correlation between LC NM contrast and the extent of motor improvement after levodopa administration 45 . They concluded that evaluating LC NM parameters using NM‐MRI might be predictive of levodopa responsiveness in PD.…”
Section: Neuromelanin Iron and The N1 Sign In Pdmentioning
confidence: 99%